Black Paul: a soul music no Brasil nos anos 1970 - Paiva, Carlos Eduardo Amaral de [UNESP] (2015)
This thesis investigates the acclimatisation of soul music genres in Brazil in the 70's by the analysing the songs of important black musicians of the era: Tim Maia, Jorge Ben and Tony Tornado as well as the movement called Black Rio. We suggest an inflection on the formation of the black identity in the country that represented the emergence of a black structure of feelings in transnational levels. This structure of feelings is chacacterised by its ethinic affirmation and its internationalism tied to black western counterculture. In a repressive political context of dictatorship, this musical movement helped bring together young black men around political identity and made a clear objection to the myth of racial democracy, the official ideology of the civil-military regime